152 Development of Deutetrabenazine as a Potential New Non-Antipsychotic Treatment for Tourette Syndrome in Children and Adolescents. (April 2020) - Jankovic, Joseph; Coffey, Barbara; Claassen, Daniel O.; Stamler, David; Gertz, Barry J.; Garofalo, Elisabeth A.; Wieman, Maria; Gordon, Mark Forrest; Savola, Juha-Matti
Abstract: Background: Tourette syndrome (TS) is a neurodevelopmental disorder characterized by the hyperkinetic movements of motor and phonic tics manifested in young age. Currently approved treatments in the United States are antipsychotics: haloperidol, pimozide, and aripiprazole, which are associated with serious side effects, including tardive dyskinesia (TD). Deutetrabenazine, a vesicular monoamine transporter type 2 (VMAT2) inhibitor, was approved in 2017 by the US FDA for the treatment of chorea associated with Huntington's disease and TD. Three ongoing studies (Alternatives for Reducing Tics in TS [ARTISTS]) are evaluating the efficacy, safety, and tolerability of deutetrabenazine in reducing tics in TS in children and adolescents (age 6-16 years). Methods: ARTISTS 1, a phase 2/3, response-driven, dose-titration, placebo-controlled study, randomizes patients (N=116) 1:1 to deutetrabenazine or placebo for 12 weeks. ARTISTS 2, a phase 3, fixed-dose study, randomizes patients (N=150) 1:1:1 to deutetrabenazine high or low dose, or placebo for 8 weeks. The primary efficacy outcome in these pivotal studies is change from baseline to end of treatment in the Total Tic Score (TTS) of the Yale Global Tic Severity Scale (YGTSS). Additional efficacy endpoints and safety/tolerability are also evaluated. ARTISTS is a 56-week, open-label, single-arm, long-term safety/tolerability study in patients who have successfully completed either ARTISTS 1 or ARTISTS 2. Results: Not available yet. Conclusion: TS can have potentially long-term life impact, and there remains unmet medical need for effective and well-tolerated treatments. Three ARTISTS studies will evaluate the efficacy, safety, and tolerability of deutetrabenazine in patients with tics in TS. Funding Acknowledgements: The studies are sponsored by Teva Pharmaceuticals and operationalized by Teva's development partner, Nuvelution TS Pharma INC.